The Use of Free Software by Brazilian Government between 2018 and 2020 - Lisboa, Flávio Gomes da Silva; Beatriz, Marilene Zazula (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2020: Anais do XVII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2020.18606, 2020)
This article presents a quantitative and qualitative exploratory research on the use of free software in the Brazilian government. The data collected refers to the period between 2018 and 2020. The motivation for the research was the lack of data on the use of free software on the government portal for this topic. Initially, the free software scenario is presented within the government's strategy since 2002 and the criticisms about the effectiveness of policies to promote free software. After explaining the methodology used for data collection, the results are presented. 87 entities were questioned, including ministries, state-owned enterprises, universities, the Federal Chamber, the Federal Senate and the Federal Supreme Court. In addition to the amount of software used, software licenses and software categories were counted, which were defined according to user rankings. State entities were also questioned about the production of free software and the results showed that, in addition to using free software, the Brazilian government also produced free software. Finally, entities were questioned about their acquisition software policies.